O ensino de Álgebra: algumas questões do ENEM e da OBMEP - Silva, Roney Feliciano da (Universidade Federal do Tocantins, 2018)
This work presents some conceptions about algebra and her teaching in high school. Such conceptions under a curricular analysis of basic education in Brazil, with respect to algebraic contents. Aiming to contribute to the formation of Mathematics teachers in Basic Education we present a study on the polynomials in which we list some properties. We address some ideas for the teaching of algebra (polynomial ring), we highlight the location of the roots of polynomial equations and their application and we present some methods for solving polynomial equations of 2o degree. We highlight the importance of teaching algebra (polynomials and polynomial functions) and its presence in two large national assessments, the National High School Examination (ENEM) and the Brazilian Mathematics Olympiad of Public Schools (OBMEP), highlighting the algebraic contents in some of these questions Assessments and presenting the resolution under an organization of three fundamental components for the teaching of mathematics: Conception, Manipulation and Application.